PERAN GURU BIMBINGAN DAN KONSELING DALAM PEMILIHAN KARIR SISWA - alvina widya utami (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
Guidance and counseling aims to enable students to find themselves, know themselves and be able to plan for their future. In this connection guidance and counseling functions as a service provider to students so that each student can develop optimally so that they become personal which can develop optimally so that they become complete and independent individuals. The teacher's role as the executor of Guidance and Counseling services in building students' discipline attitude is as a guide and collaborator only, while the teacher's role is as a mediator. This type of research uses descriptive qualitative research. The subject of this research is a guidance and counseling teacher. Based on the research results obtained from the interviews, the researchers found the role of the guidance and counseling teacher including, the guidance and counseling teacher had carried out the role by providing assistance/services in accordance with the guidance and counseling service component